Correlation between Kidney Failure Disease and Parathyroid Gland with Family Genetic History - Eljamay, Salwa Muftah; Asrafel, Hameda (Indonesian Journal of Community Services, 2024)
Family-based and genome-wide studies suggest that genetic differences significantly influence an individual’s lifetime risk for kidney disease. Aimed to: find out if there are relationship between kidney failure disease and family genetic history. Material and Methods: Data were collected using interviewer-administered questionnaires. Data from the biochemical analysis and questionnaire with a Google form survey were recorded in Microsoft Excel. Results: The percentage of Gender for hemodialysis patients males 61(57.6%) more than females 45(42.5%), the correlation between age and other variables is quite weak (R = 0.098, P = 0.315). Gender also shows a weak correlation with other variables (R = 0.049, P = 0.616). There is a significant correlation between having a family member with a parathyroid gland issue and other factors (R = 0.248, P < 0.010). The strongest correlation found is between having a family member who suffers or has suffered from kidney failure and other factors (R = 0.277, P = 0.004). Conclusion:  The weak correlations with age and gender indicate that these factors might not be central to the study's main findings. The strongest correlation found is between having a family member who suffers or has suffered from kidney failure and other factors.